Assessing leasing as a major alternative financing mechanism for SMES in Ghana: a case study of selected SMES in the Accra metropolis. - Boafo, Yaw Afriyie (2025)
Dissertation Submitted In Partial Fulfillment Of The Requirement For Award Of Master Of Science Degree In Economics.